Researching research affects: in-between different research positions. (June 2022) - Johansson, Lotta; Moe, Merete; Nissen, Kjersti
A significant amount of research has highlighted the different ontological and epistemological dimensions of insider and outsider research positions. In the field of education, this topic could benefit from more research. In this study, three researchers and former early childhood centre directors discussed their own research positions in a completed research project. Based on field notes from following the daily work of the centre leaders – positions the researchers formally held themselves – it is illustrated that the research affects continued to flow after the project had ended, raising new questions about how specific situations and the data had been handled. This study, a folding, unfolding and re-folding of data, highlights the ethical considerations actualised in the movements between research positions. The movements between research positions are understood as a source of tension that can produce affects, becomings and data with the ability to question given positions and established knowledge.